Prediction of adsorption equilibria from physical properties of the pure components - Schürer, Gudrun; Peukert, Wolfgang (Adsorption-Journal of the International Adsorption Society, 2005)
The prediction of adsorption energies equilibria is often based on mixed terms influenced by both the adsorptive and the adsorbent. Our aim is to predict adsorption equilibria by using physical properties of the pure components. Based on the concept of equivalent surface properties we introduce models using one or two mean parameters (Hamaker constant, mean partial charge) as well as a model which takes partial charge distributions into account. Density functional theory (DFT) calculations can be used to describe well defined and regular surfaces. However, the structure and topology of heterogeneous surfaces are generally unknown. Thus the combination of DFT-calculations with a continuum solvation model and experimental data allows the prediction of the adsorption equilibrium at infinite dilution. For activated carbon in the gas phase and in water the Henry’s law coefficients obtained by this method cover a range of 7 orders of magnitude. In order to gain a better understanding of the role of heterogeneities, DFT-calculations of model surfaces like functionalized coronenes or fullerenes were performed. A good qualitative agreement with the experimentally determined results was observe
Keywords: Activated carbon; COSMO-RS; Adsorption equilibria prediction; Henry's law coefficient